Silicon incorporated morpholine antifungals: design, synthesis, and biological evaluation - Jachak, Gorakhnath R.; Ramesh, Remya; Sant, Duhita G.; Jorwekar, Shweta U.; Jadhav, Manjusha R.; Tupe, Santosh G.; Deshpande, Mukund V.; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Known morpholine class antifungals (fenpropimorph, fenpropidin, and amorolfine) were synthetically modified through silicon incorporation to have 15 sila-analogues. Twelve sila-analogues exhibited potent antifungal activity against different human fungal pathogens such as Candida albicans, Candida glabrata, Candida tropicalis, Cryptococcus neoformans, and Aspergillus niger. Si la-analogue 24 (fenpropimorph analogue) was the best in our hands, which showed superior fungicidal potential than fenpropidin, fenpropimorph, and amorolfine. The mode of action of sila-analogues was similar to morpholines, i.e., inhibition of sterol reductase and sterol isomerase enzymes of ergosterol synthesis pathway.
Keywords: Antifungal drugs; Candida albicans; ergosterol biosynthesis; morpholines; sila-analogues

Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition

Re-engineering of PIP3-antagonist triazole PITENIN's chemical scaffold: development of novel antifungal leads - Pulya, Sravani; Kommagalla, Yadagiri; Sant, Duhita G.; Jorwekar, Shweta U.; Tupe, Santosh G.; Deshpande, Mukund V.; Ramana, Chepuri V. (RSC Advances, 2016)
A novel 4-(1-phenyl-1-hydroxyethyl)-1-(o-hydroxyphenyl)-1H-1,2,3-triazole was designed by integrating the structural features of triazole PITENIN anticancer agents and the azole class of antifungal drugs. A two-step protocol comprising the Barbier propargylation and Cu-catalyzed azide-alkyne cycloaddition was established to synthesise a diverse set of compounds of this class. Their screening against a wide range of human fungal pathogens led to identification of several potential antifungal hits and some of them displayed better antifungal activity than fluconazole against Candida glabrata, Cryptococcus neoformans, Aspergillus fumigatus and Aspergillus niger. Mode of action studies revealed that their antifungal activity was resulting either from the inhibition of lanosterol 14 alpha-demethylase enzyme (leading to ergosterol depletion) or by the generation of reactive oxygen species (ROS).